Household Food Waste Management in Rural Communities: A Knowledge, Attitude, and Practice Study - Sholihah, Salma Mar'atus; Tumuyu, Sri Setiawati; Herdiansyah, Herdis (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Households are the largest contributors to food waste in Indonesia. Rural communities often lack effective waste management infrastructure, making it essential to promote low-cost, sustainable alternatives like maggot cultivation to reduce organic waste and support local agriculture. A questionnaire survey of 114 householders was performed on Kertajaga residents to assess their knowledge, attitude, and practice (KAP) towards food waste management, including refuse, reduce, reuse, recycle, and participation in the organic waste bank. The study analyzes the association between knowledge, attitude, and practice. The study also covered the relationship between sociodemographic variables and KAP towards household food waste management. The respondents were divided into two categories: waste bank customers and non-customers, whose differences in KAP levels were also assessed in this research. There is a significant difference between customer and non-customer knowledge, but it is not found in attitude and practice. The main finding of this study is that knowledge of food waste management in rural households is generally good and significantly influenced by socialization activities, while attitudes and practices remain moderate with varied associations to sociodemographic factors. A study regarding the content and forms of waste management socialization that are suitable and acceptable for low-income rural communities needs to be carried out to increase the effectiveness of household food waste management in rural areas.